Heme Oxygenase-1/Ferritin in Protection of Leukemia Cells from Oxidative Stress Induced by Catalytic System "Teraphtal + Ascorbic Acid" - TA Sidorova; OO Ryabaya; AA Prokof’eva; DA Khochenkov (Клиническая онкогематология)

(untitled)
Background. As is well known, cytotoxic mechanism of antitumor agent, i.e. catalytic system “teraphtal + ascorbic acid” (“TF+AA”), is associated with production of reactive oxygen species (ROS) and induction of oxidative stress in it. The “heme oxygenase-1/ferritin” (HО-1/Ft) system contributes to antioxidant defense.